2017
DOI: 10.1002/joc.5334
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and projection of extreme precipitation indices in the Eastern Mediterranean based on CMIP5 multi‐model ensemble

Abstract: An evaluation of 23 models, participating in the Coupled Model Inter‐comparison Project phase 5 (CMIP5), in representing extreme precipitation indices (EPI), over the Eastern Mediterranean (EM) and the Fertile Crescent (FC), was performed. The models ensemble was then used to predict the EPIs evolution in the 21st century under (Representative Concentration Pathway, RCP) RCP4.5 and RCP8.5 scenarios. Models' performance was determined with respect to gridded precipitation observations from the APHRODITE project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 51 publications
(99 reference statements)
4
47
0
Order By: Relevance
“…A projected tendency towards drier conditions is confirmed by the simulation for the Mediterranean climate and semi-arid climate of Israel, in agreement with low-resolution projections (Samuels et al, 2017). Note that the absolute precipitation amounts are very different between the northern Mediterranean climate and the southern arid climate; the region showing projected reductions in precipitation is larger than the region showing increases.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…A projected tendency towards drier conditions is confirmed by the simulation for the Mediterranean climate and semi-arid climate of Israel, in agreement with low-resolution projections (Samuels et al, 2017). Note that the absolute precipitation amounts are very different between the northern Mediterranean climate and the southern arid climate; the region showing projected reductions in precipitation is larger than the region showing increases.…”
Section: Discussionsupporting
confidence: 85%
“…Accordingly, climate projections over the 21st century have been conducted adopting the same spatial resolutions. Initial and boundary conditions were derived by the global climate model CMCC-CM (Scoccimarro et al, 2011), which was found to represent EPI in the EM relatively well (Samuels et al, 2017). Initial and boundary conditions were derived by the global climate model CMCC-CM (Scoccimarro et al, 2011), which was found to represent EPI in the EM relatively well (Samuels et al, 2017).…”
Section: Data and Setup Of Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…dkrz.de/WDCC/ui/Index.jsp) data portal. These models were previously utilized in Hochman et al (2018b, c, and2019) (list of models see Table 1) and their ability to simulate annual and extreme precipitation indices over the eastern Mediterranean was previously presented by Samuels et al (2017). Furthermore, these models' ability to simulate the annual cycle of the prevailing eastern Mediterranean synoptic systems, their frequencies, and dynamics for the historical period were presented in Hochman et al (2018b, c, and2019).…”
Section: Datamentioning
confidence: 99%